Dampak PPKM Terhadap Sampah Plastik di Jakarta - Mohammad Ananda Reza Kurniawan; Athila Safira Rahma (Universitas Indraprasta PGRI, 2022)
The COVID-19 pandemic in Indonesia is not over yet. In Jakarta, the transmission rate of COVID-19 is still very high. At this time people are asked to work from home, this encourages an increase in online shopping where every item sent will be wrapped in plastic. It also encourages increased use of plastic and generates plastic waste. The purpose of this study was to determine the impact of PPKM on plastic waste in Jakarta. This research was carried out on the community in Jakarta online. The method used is descriptive qualitative. In this case, researchers want to analyze plastic waste resulting from the impact of PPKM, namely working from home which encourages increased online shopping. The subjects of this research are Jakarta residents who work from home and do online shopping and get 100 respondents. The results of this study found that within one month there was a decrease from the data 1-5 times in one month by 6%, and an increase in data 6 -10, 11-15 times, 16-20 times, 21-25 times and 26-30 times in a month are 3%, 1%, 2%, 1%, and 1%, respectively, while for those who do not spend online and 30 times have fixed results. Other results show that 49% of online shopping items are wrapped in plastic. plastic as a wrapping material that causes the production of plastic waste in household waste in DKI Jakarta because 49% of the packaging materials for goods, both packages and other shipments, use plastic materials.